COMPARISON OF SUBLINGUAL MISOPROSTOL VERSUS INTRAVENOUS OXYTOCIN FOR REDUCING MEAN BLOOD LOSS AFTER VAGINAL DELIVERY - KHAN, MA; PARVEEN, M; SADIQ, S; UMAIR, RM; KAINAT, S (Biological and Clinical Sciences Research Journal, 2022)
Postpartum hemorrhage (PPH) is significantly associated with maternal morbidity and mortality, and many maternal deaths are preventable. Uterine atony is managed through uterotonic agents like prostaglandin F2 alpha (PGF2a), misoprostol, ergometrine and oxytocin and uterine rubbing. This prospective study was designed to compare the role of sublingual misoprostol and IV oxytocin in preventing blood loss after vaginal deliveries. This study was conducted at the Department of Obstetrics & Gynecology, Nishtar Hospital Multan, from 15 February 2021 to 14 August 2021. The study was conducted on 60 patients, 30 in both groups, who were selected through consecutive nonprobability sampling. Subjects were divided into Group A and Group B. 600 µg misoprostol (3 doses of 200 µg) was administered to Group A. 5 IU oxytocin was administered to Group B, with 3.3 IU/min at the beginning with the interval of 20 minutes until regular contractions are achieved. A maximum of 30mU/min oxytocin was infused. Mean blood loss was measured and recorded in proforma. The mean age of the subjects was 29.21 ± 6.07 years. The mean age of Group A was 29.40 ± 5.85 years, while that of Group B was 29.21 ± 6.32 years. Mean PPH blood loss in Group A, and B was 118.97 ± 20.26 ml and 154.13 ± 15.21 ml (P = 0.0001). The mean postpartum blood loss was higher by intravenous oxytocin than by sublingual misoprostol.